2010
DOI: 10.1007/s11695-010-0343-4
|View full text |Cite
|
Sign up to set email alerts
|

Routine Abdominal Drains after Laparoscopic Sleeve Gastrectomy: A Retrospective Review of 353 Patients

Abstract: Complications after laparoscopic sleeve gastrectomy (LSG) are usually silent and difficult to interpret. Our purpose was to evaluate the utility of routine placement of intraperitoneal drains at the end of LSG in detection and management of postoperative complications. This is a retrospective study of all patients that underwent LSG by a standard operative team in a 3-year period. Patients were enrolled in Group A when an intraperitoneal drain was placed and Group B when not. Three hundred and fifty-three pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 17 publications
2
27
0
Order By: Relevance
“…Based on our findings, comparable with those achieved by Rossetti et al (7), the NGT does not show to have any role in the prevention of gastric fistula neither in the diagnosis of intraluminal hemorrhage af- (11). Moreover, as already described by Albanopoulos K. et al (6) and as reported in two cases of bleeding of our series (group A), in the majority of cases of staple line bleeding or leakage, drainage is silent and does not allow surgeon to suspect such complications which are often revealed by other clinical signs as fever/tachycardia/vomit or by laboratory test as drop in hemoglobin value or by diagnostic imaging as peri-gastric fluid collection on abdominal ultrasound/tomography. In gastric surgery, drain placement is designed for the removal of fluid collections or for the early detection of post-operative bleeding, gastric fistulas, and intra-abdominal infections.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Based on our findings, comparable with those achieved by Rossetti et al (7), the NGT does not show to have any role in the prevention of gastric fistula neither in the diagnosis of intraluminal hemorrhage af- (11). Moreover, as already described by Albanopoulos K. et al (6) and as reported in two cases of bleeding of our series (group A), in the majority of cases of staple line bleeding or leakage, drainage is silent and does not allow surgeon to suspect such complications which are often revealed by other clinical signs as fever/tachycardia/vomit or by laboratory test as drop in hemoglobin value or by diagnostic imaging as peri-gastric fluid collection on abdominal ultrasound/tomography. In gastric surgery, drain placement is designed for the removal of fluid collections or for the early detection of post-operative bleeding, gastric fistulas, and intra-abdominal infections.…”
Section: Discussionsupporting
confidence: 91%
“…Literature is lacking of prospective studies and surgeons are still not fully confident of avoiding gastric decompression and peritoneal cavity drainage (5). In the only two reports written respectively by Albanopoulos K et al in 2011 (6) and Rossetti G et al in 2014 (7) it has been preliminarily shown how NGT and IAD do not really influence the post-operative outcome in terms of lower surgical morbidity rate. Moreover, NGT and IAD represents post-operatively a serious diLaparoscopic sleeve gastrectomy for morbid obesity: role of intraluminal and intraperitoneal postoperative drainage scomfort for patients who often refer nausea and throat pain related to NGT and abdominal pain due to IAD.…”
Section: Introductionmentioning
confidence: 99%
“…In our patients, a drain did not allow us to detect the leak nor was it useful in its treatment. Albanopoulos et al in a prospective double-blind study support this observation [21].…”
Section: Discussionmentioning
confidence: 80%
“…All patients received methylene blue solution on the second postoperative day, as this is included in the standard postoperative evaluation protocol of our department [8]. Patients with negative methylene blue solution test who presented fever, abdominal pain, or serious tachycardia underwent upper gastrointestinal series (UGIS) or abdominal CT with water-soluble contrast.…”
Section: Methodsmentioning
confidence: 99%
“…The surgeon stands between the patient's legs and a fivetrocars technique is used as we have previously described [8]. An optiview trocar (Ethicon Endo-Surgery, Cincinatti Ohio) is used for entering in the peritoneal cavity and dissection of the greater omentum is performed with the use of the LCSC5 Coagulating Shear (Ethicon Endo-Surgery, Inc).…”
Section: Operative Techniquementioning
confidence: 99%